Evaluating Copper-Doped Biochar Composites for Improving Wheat Nutrition and Growth in Oxisols - Loren Chisté; Carlos Alberto Silva; Flávio Henrique Silveira Rabêlo; Keiji Jindo; Leônidas Carrijo Azevedo Melo (Agronomy)
Copper (Cu) is a critical micronutrient for wheat (Triticum aestivum L.), essential for growth and grain baking quality, yet its availability is limited because Cu is specifically adsorbed on colloids of highly weathered tropical soils like Oxisols. This study hypothesizes that Cu-doped biochar composites can outperform traditional Cu fertilizers in improving wheat growth and Cu use efficiency. Composites were synthesized from chicken manure (FCM), shrimp shells (FSC), and sewage sludge (FSS), doped with copper sulfate (CuSO45H2O) or copper oxide (CuO), and pyrolyzed at 300 °C or 550 °C. The experimental design involved greenhouse trials in two Oxisols (RYL and DRL), assessing Cu release kinetics, plant Cu uptake, and dry matter production. Fourier Transform Infrared Spectroscopy (FTIR) confirmed successful Cu integration. Results revealed that CSS/CS-5 (FSS + CuSO45H2O at 550 °C) improved Cu uptake and shoot biomass in DRL soil, while CSC/CS-3 (FSC + CuSO45H2O at 300 °C) enhanced wheat CuSO45H2O growth in RYL soil. Peak Cu availability varied by CuSO45H2O soil and composite type, with residual Cu highest CuSO45H2O in CuSO45H2O-treated soils. These findings demonstrate that Cu–biochar composites, tailored to soil conditions, offer a sustainable alternative to mineral Cu fertilizers by enhancing the nutrient availability and wheat grain yield.